Impact of facial angiofibromas in tuberous sclerosis complex and reported efficacy of available treatments - Monaghan, Marie; Takhar, Pooja; Langlands, Luke; Knuf, Markus; Amin, Sam (Frontiers in Medicine, 2022)
Tuberous Sclerosis Complex (TSC) is a genetic condition which leads to a loss of inhibition of cellular growth. Facial angiofibromas (FAs) are hamartomatous growths associated with TSC that appear as multiple small, erythematous papules on the skin of the face and may resemble more severe forms of acne vulgaris. FAs have been reported in up to 74.5% of pediatric TSC patients, rising to up to 88% in adults >30 years old. They have not been closely studied, potentially overshadowed by other, systemic features of TSC. To investigate the impact of FAs, a common clinical feature for patients with TSC, we performed a non-interventional study in the form of a survey, completed by people living with TSC and FAs, or their caregiver as a proxy, if necessary. Patients were recruited via patient organizations in the UK and Germany. Data was received from 108 families in the UK (44 patients, 64 caregivers) and 127 families in Germany (50 patients, 64 caregivers). Exclusion criteria were those outside of 6-89 years, those without FAs, or those enrolled in a clinical trial. Where caregivers reported on behalf of an individual unable to consent, they were required to be adults (>18 years). Patient experience in the design of the survey was considered from practical and logistical perspectives with survey questions assessing multiple aspects relating to FAs including age of onset, perceived severity, treatments, perceived efficacy of treatments and perceived psychosocial impacts of the FAs. The psychosocial impacts of FAs for the individuals as well as for caregivers were explored in terms of social, occupational and leisure activities. Results of the survey demonstrated that for those with TSC-related moderate or severe FAs, there is an impact on quality of life and psychosocial impacts in the form of anxiety and depression. This finding was also noted by caregivers of TSC individuals in these categories. The treatment most frequently received to improve FAs, topical rapamycin/sirolimus, was found to be successful in the majority of those who received it.